Enhancing learning of foreign languages through film subtitling / Liaw Shun Chone … [et al.] - Liaw, Shun Chone (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2010)
The learning of foreign languages has always been a daunting task for both learners and educators. The existing learning tools do not cater for effective foreign language learning. FoLLetS courseware attempts to address this problem by incorporating audio, visual and text (via subtitles). In using FoLLetS, learners have autonomy in the learning process. In this study, 30 elementary learners of French, Mandarin and Japanese evaluated the courseware and the majority found it useful in enhancing their learning of foreign languages through film subtitling. They also provided comments on the strengths and weaknesses of the courseware.